Fixed Points for Multivalued Mappings in b-Metric Spaces. (22nd March 2015) - Jleli, Mohamed; Samet, Bessem; Vetro, Calogero; Vetro, Francesca
Abstract : In 2012, Samet et al. introduced the notion of α - ψ -contractive mapping and gave sufficient conditions for the existence of fixed points for this class of mappings. The purpose of our paper is to study the existence of fixed points for multivalued mappings, under an α - ψ -contractive condition of Ćirić type, in the setting of complete b -metric spaces. An application to integral equation is given.